2020
DOI: 10.7554/elife.57951
|View full text |Cite
|
Sign up to set email alerts
|

Stress-activated MAPK signaling controls fission yeast actomyosin ring integrity by modulating formin For3 levels

Abstract: Cytokinesis, which enables the physical separation of daughter cells once mitosis has been completed, is executed in fungal and animal cells by a contractile actin- and myosin-based ring (CAR). In the fission yeast Schizosaccharomyces pombe the formin For3 nucleates actin cables and also co-operates for CAR assembly during cytokinesis. Mitogen-Activated Protein Kinases (MAPKs) regulate essential adaptive responses in eukaryotic organisms to environmental changes. We show that the Stress Activated Protein Kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 68 publications
3
27
0
Order By: Relevance
“…Since b-estradiol is not a yeast metabolite or signaling molecule, cellular metabolism is not perturbed (McIsaac et al, 2013b). ZEVs have been widely used for basic and applied research, including studies of gene regulatory networks (Hackett et al, 2020;Kang et al, 2020;Ma & Brent, 2020), individual gene function (Elfving et al, 2014;Lyon et al, 2016;Weir et al, 2017;Tran et al, 2018;Kim et al, 2019;Smith et al, 2020;Wang et al, 2020;Kira et al, 2021), gene regulation (Carey, 2015;Hendrickson et al, 2018a;Schikora-Tamarit et al, 2018;Lutz et al, 2019;Brion et al, 2020;preprint: Leydon et al, 2021), metabolic engineering (Liu et al, 2020), synthetic biology (Schikora-Tamarit et al, 2016;Aranda-D ıaz et al, 2017;Gander et al, 2017;Pothoulakis & Ellis, 2018;Bashor et al, 2019;Kotopka & Smolke, 2020;Shaw et al, 2019;Yang et al, 2019), biocontainment (Agmon et al, 2017), living materials (Gilbert et al, 2021), highthroughput screening (Younger et al, 2017;Staller et al, 2018), and they have also been adapted to fission yeast (Ohira et al, 2017;G omez-Gil et al, 2020;Nuckolls et al, 2020) and Pichia pastoris (Perez-Pinera et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since b-estradiol is not a yeast metabolite or signaling molecule, cellular metabolism is not perturbed (McIsaac et al, 2013b). ZEVs have been widely used for basic and applied research, including studies of gene regulatory networks (Hackett et al, 2020;Kang et al, 2020;Ma & Brent, 2020), individual gene function (Elfving et al, 2014;Lyon et al, 2016;Weir et al, 2017;Tran et al, 2018;Kim et al, 2019;Smith et al, 2020;Wang et al, 2020;Kira et al, 2021), gene regulation (Carey, 2015;Hendrickson et al, 2018a;Schikora-Tamarit et al, 2018;Lutz et al, 2019;Brion et al, 2020;preprint: Leydon et al, 2021), metabolic engineering (Liu et al, 2020), synthetic biology (Schikora-Tamarit et al, 2016;Aranda-D ıaz et al, 2017;Gander et al, 2017;Pothoulakis & Ellis, 2018;Bashor et al, 2019;Kotopka & Smolke, 2020;Shaw et al, 2019;Yang et al, 2019), biocontainment (Agmon et al, 2017), living materials (Gilbert et al, 2021), highthroughput screening (Younger et al, 2017;Staller et al, 2018), and they have also been adapted to fission yeast (Ohira et al, 2017;G omez-Gil et al, 2020;Nuckolls et al, 2020) and Pichia pastoris (Perez-Pinera et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To distinguish the requirement of actin cables and the CAR for nuclear movement, we treated cut7-22 cells with a lower concentration (0.15 μM) of LatA, the condition of which reportedly blocks actin cable formation, whereas CAR assembly and constriction proceed ( Gomez-Gil et al., 2020 ; Tournier et al., 2004 ). We found that under this low concentration of LatA, mitotic actin cables disappeared and ∼70% of cut7-22 cells (17/24) were capable of assembling and constricting the CAR ( Figures 5 A–5C).…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, the SAPK pathway and its effector, MAPK Sty1, elicit CAR disassembly in S. pombe when its integrity becomes compromised during actin damage and stress by downregulating For3 levels, thereby blocking cell division until the damage is repaired. The molecular mechanism that controls For3 under these circumstances seems Cdc42 independent, but its participation cannot be completely ruled out [91].…”
Section: Rho Signaling In Cytokinesis 61 Schizosaccharomyces Pombementioning
confidence: 99%